De Novo Transcriptomic Analysis of an Oleaginous Microalga: Pathway Description and Gene Discovery for Production of Next-Generation Biofuels - Wan, LingLin; Han, Juan; Sang, Min; Li, AiFen; Wu, Hong; Yin, ShunJi; Zhang, ChengWu (PLOS ONE, 2012)
Background Eustigmatos cf. polyphem is a yellow-green unicellular soil microalga belonging to the eustimatophyte with high biomass and considerable production of triacylglycerols (TAGs) for biofuels, which is thus referred to as an oleaginous microalga. The paucity of microalgae genome sequences, however, limits development of gene-based biofuel feedstock optimization studies. Here we describe the sequencing and de novo transcriptome assembly for a non-model microalgae species, E. cf. polyphem, and identify pathways and genes of importance related to biofuel production. Results We performed the de novo assembly of E. cf. polyphem transcriptome using Illumina paired-end sequencing technology. In a single run, we produced 29,199,432 sequencing reads corresponding to 2.33 Gb total nucleotides. These reads were assembled into 75,632 unigenes with a mean size of 503 bp and an N50 of 663 bp, ranging from 100 bp to >3,000 bp. Assembled unigenes were subjected to BLAST similarity searches and annotated with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) orthology identifiers. These analyses identified the majority of carbohydrate, fatty acids, TAG and carotenoids biosynthesis and catabolism pathways in E. cf. polyphem. Conclusions Our data provides the construction of metabolic pathways involved in the biosynthesis and catabolism of carbohydrate, fatty acids, TAG and carotenoids in E. cf. polyphem and provides a foundation for the molecular genetics and functional genomics required to direct metabolic engineering efforts that seek to enhance the quantity and character of microalgae-based biofuel feedstock.